2019
DOI: 10.1111/phn.12587
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality is associated with obesity and depression in farmers

Abstract: Background Farmers’ work schedules can result in inconsistent sleep patterns which negatively impact health. Purpose To explore the relationships between sleep, obesity, and depression in working, older farmers and their spouses. Covariates included body mass index (BMI), age, and gender. Methods Sleep quality, BMI, and depression were assessed in farmers (n = 1,394) 50 years and older. Bivariate associations among all covariates (i.e., age, gender, BMI, sleep) and dependent variable (i.e., depression) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 33 publications
2
20
1
4
Order By: Relevance
“…In addition, Poor quality of sleep is in association with anxiety and depression. [31][32][33][34][35][36][37][38][39] Our results share several similarities with Potvin et al's ndings, which reported a signi cant association of PSQI subscales with anxiety, particularly sleep duration in hours, sleep disturbance score, and daytime functioning score. [40] Since sleep is a complex biological process, providing an exact pathophysiological theory as a justi cation of reported correlations between poor sleep quality, depression and anxiety have been a subject of controversy.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, Poor quality of sleep is in association with anxiety and depression. [31][32][33][34][35][36][37][38][39] Our results share several similarities with Potvin et al's ndings, which reported a signi cant association of PSQI subscales with anxiety, particularly sleep duration in hours, sleep disturbance score, and daytime functioning score. [40] Since sleep is a complex biological process, providing an exact pathophysiological theory as a justi cation of reported correlations between poor sleep quality, depression and anxiety have been a subject of controversy.…”
Section: Discussionsupporting
confidence: 86%
“…It has been found that farm residents with self-reported physical illness (e.g., neck, shoulder, and back pain [73]; obesity; metabolic syndrome; abdominal adiposity; and cardiovascular disease [153,154]) tend to have higher self-reported psychiatric impairment. Hawes et al [155] found that higher body mass index (BMI) and poor sleep quality were also associated with higher depression scores. Carvalho et al [156] found an association between work end time on the relationship between sleep onset time and farmer psychological well-being.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Usually lack of knowledge or the belief that a person should deal with his or her mental problems alone were common reasons that decrease the possibility of individuals’ help-seeking [9,58,179]. Lack of access to mental health services in rural areas was another major burden to the delivery of appropriate mental health services [20,33,155]. Polain et al [181] found that usually, older farmers try to access mental health support; however, practical and cultural barriers often prevented them from succeeding.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Six studies (Beseler & Stallones, 2003;Hawes et al, 2019;Merchant et al, 2002;Rayens & Reed, 2014;Stallones & Beseler, 2002b, 2004 confirmed that women exhibited higher depressive symptoms scores compared to men in the study; no studies reported higher rates in men compared to women. Carruth and Logan (2002) noted that 24% of their all-female sample reported depression, while Scarth et al (2000) reported a prevalence of 9.8% in their all male sample.…”
Section: Factors Affecting Farmers' Depressive Symptoms and Suicide Gmentioning
confidence: 63%